Comparison on the efficacy of immediate release oxycodone and tramadol in reducing postoperative pain, nausea and vomiting in post laparotomy patients weaned from PCA morphine - Kumar, Shyamala a/p V. (2016)
Introduction : The introduction of oxycodone into the Malaysian health care system in recent years has opened up another option for postoperative pain relief. We assess the clinical efficacy of oral oxycodone IR in reducing pain as well as nausea and vomiting and compare it to oral tramadol in this postoperative study. Objective: This was a prospective, randomised, double blinded study on the efficacy of oxycodone IR as oral maintenance analgesia in reducing postoperative pain, analgesic requirement and incidence of nausea and vomiting in patients post laparotomy after PCA morphine is weaned off. This study was conducted in Hospital Universiti Sains Malaysia. Methodology : We recruited 40 patients undergoing an elective laparotomy for gynaecological surgery. These patients were randomly selected to receive oral oxycodone IR once PCA morphine was weaned off 48 hours post surgery. The other group of patients received the standard oral tramadol. Postoperative pain scores were assessed using the Combination Rating Scale and requirement of rescue analgesia at 2 hours, 6 hours, 24 hours and on day 3 of oral analgesia. Incidence of nausea was documented along with the requirement of rescue antiemetics at the same intervals. Assessment was made by pain services nurses and data was entered using Statistical Package for Social Science SPSS Version 22. Results: This study revealed that patients receiving oral oxycodone IR had significantly lower pain scores of less than 4 which was achieved within 6 hours of treatment. This level was only achieved by the tramadol group at 24 hours of treatment. This is significant with a p value < 0.001 based on time and treatment effects. Requirement of 1st and 2nd line rescue analgesia was significant between groups. 10% of the oxycodone group and 60% of the tramadol group needed 1st line rescue and 5% of the oxycodone group against 40% of the tramadol required rescue analgesia. Incidence of nausea was significantly lower in the oxycodone group only at 2 hours with a p value of 0.022. The requirement of 1st and 2nd line rescue antiemetics was lower in the oxycodone group however remained insignificant with a p value of > 0.05. Finally the mean satisfaction score for patients on oxycodone was 6.85 compared to 5.75 over a score of 10 with a significant mean difference of p value < 0.001. Conclusion : The introduction of oral oxycodone IR in the postoperative period for post laparotomy patients who were weaned from PCA morphine showed better pain scores and less analgesic requirement. These patients also had reduced incidence of nausea at 2 hours and better overall patient satisfaction scores compared to the tramadol group. However, there was no significant difference in the antiemetic requirement between the two groups